Rural Digital System for Optimizing Yellow Corn Product Results - Ummiati Rahmah; Citra Ayni Kamaruddin; Mahmud Mustapa; Bobur Sobirov (Yayasan Cendekiawan Digital Indonesia, 2025)
Polongbangkeng Utara, a region in Takalar Regency, is known for its agricultural production, particularly rice and yellow corn. However, despite its potential, corn has traditionally been sold only in its raw kernel form, limiting the economic benefits for local farmers. To address this issue, there is a pressing need to educate the community on processing and marketing corn-based products through Micro, Small, and Medium Enterprises (MSMEs) by leveraging digital social media platforms. This community service initiative aims to enhance local knowledge on optimizing yellow corn utilization to increase income, develop applications to support yellow corn production, assist start-ups in yellow corn agribusiness, and provide training on utilizing marketplaces and e-marketing strategies through Android-based applications. Additionally, it seeks to diversify corn-based products, introduce innovative product designs, and offer interactive media and training modules for corn processing. The initiative received a highly positive response from the Biralle Kunyi farmer group and State Junior High School (SMP) Negeri 4 Polongbangkeng Utara, the program's target groups. Implemented in two phases, the program successfully improved the knowledge and technical skills of participants in processing yellow corn into value-added food products and effectively marketing them via social media. As a result, the digitalization process was optimized, significantly supporting the promotion and commercialization of processed yellow corn products, thereby contributing to the region’s economic growth.